PAI Teachers Strategy Effectiveness in The New Nomal State Teacher Learning at Plandaan Jombang High School - Mohammad Saat Ibnu Waqfin; Amallia Nur Aini (SCHOOLAR: Social and Literature Study in Education, 2022)
The impact of the Covid 19 pandemic led to an online learning process. Online learning is learning that is done online, using learning applications and social networks. The objectives of this study are: 1) to know the effectiveness of online learning at Plandaan Jombang State High School, 2) to know online learning strategies for teachers at Plandaan Jombang State High School. The method that researchers use is qualitative in the form of deciphering, digging information, describing. The result of this study is the effectiveness of teacher strategy in online learning. The learning strategy used by teachers in PAI learning during the pandemic at Plandaan Jombang State High School was conducted by using learning strategies using whatsapp group media. By using learning strategies using whatsapp group media teachers are easier to communicate with students. By providing material through whatsapp groups in the form of textbooks, PPT, videos and others.During online learning using whatsapp group strategy, learning goes well, smoothly and effectively. Students can follow the learning well.